2023
DOI: 10.1039/d2ra07177k
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent hydrogen bond-mediated vibrational coupling of amide I

Abstract: The involvement of amide I in vibrational coupling with symmetric and asymmetric CC modes of different phenolic derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18] Considering that HDS and HER involve hydrogenation and dehydrogenation processes, which are inverse reactions, the activity and correlation of Co-Mo-S based catalysts between these two reactions are worthy of indepth investigation. 19,20 It has been found that the size, morphology and structure of MoS 2 have a certain correlation with its catalytic activity. 21,22 Studies have shown that the Co promotes MoS 2 based catalysts which have high performance for HER, are also active for HDS.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] Considering that HDS and HER involve hydrogenation and dehydrogenation processes, which are inverse reactions, the activity and correlation of Co-Mo-S based catalysts between these two reactions are worthy of indepth investigation. 19,20 It has been found that the size, morphology and structure of MoS 2 have a certain correlation with its catalytic activity. 21,22 Studies have shown that the Co promotes MoS 2 based catalysts which have high performance for HER, are also active for HDS.…”
Section: Introductionmentioning
confidence: 99%